Vote for Peace - Implementation and Performance of a Parallel Operating System - Schröder-Preikschat, Wolfgang; et al. (IEEE Concurrency, 1997)
Vote, a virtual shared-memory system and an extension to the Peace parallel operating system, provides architectural transparency and efficiency to effectively solve high-performance computing problems.
UnivIS-Import:2015-03-05:Pub.1997.tech.IMMD.IMMD4.votefo